Re-examination of successful agers with lower biological than chronological age still after a 20-year follow-up period - Viljanen Anna; Salminen Marika; Irjala Kerttu; Korhonen Päivi; Vahlberg Tero; Viitanen Matti; Löppönen Minna; Viikari Laura (BMC, 2025)
Background: Successful ageing is the term often used for depicting exceptional ageing but a uniform definition is lacking. The aim was to re-examine and describe the successful agers living at home at the age of 84 years or over after a 20-year follow-up. The purpose was also to identify possible factors leading to their successful ageing.
Methods: Successful ageing was defined as the ability to live at home without daily care. Data on the participants' functional ability, objective health, self-rated health and satisfaction with life were gathered at baseline and after a 20-year follow-up period. A measurement of personal biological age (PBA) was established and the difference between the PBA and the chronological age (CA) was counted.
Results: The participants' mean age was 87.6 years (Standard deviation 2.5, range 84-96). All analyzed variables depicted poorer physical ability and subjective health at re-examination than at baseline. Still, 99% of the participants were at least moderately satisfied with their lives. The PBA at baseline was 6.5 years younger than CA, and at re-examination, the difference was even more pronounced at 10.5 years.
Discussion: Even though the participants were chronologically older, had poorer physical ability and subjective health, they were still satisfied with their lives indicating possible psychological resilience. The difference between the PBA and CA was greater at re-examination than at baseline indicating that they were also biologically successful agers.
Conclusions: Successful agers were satisfied with life despite hardships and had a lower biological than chronological age. Further research is needed to evaluate causality.